Possibility to adopt LRTAP against Transboundary Haze Pollution: What Should ASEAN Look For? - Umar, Wahyudi; Kurrahman, Taufik (Indonesian Comparative Law Review, 2022)
Transboundary pollution is part of air pollution originating from other countries has an impact on areas that are under the jurisdiction of other countries, The seasonal haze affected the health quality of ASEAN, it is evident that every time a forest fire occurs, the population with respiratory problems increases, including psychological stress. The objective of this paper is to investigate the problems and challenges that ATHP faces. It elaborates on the factors that contributed to LRTAP's relative success. It also analyzes and describes the measures taken in relation to the ATHP and compares its efficacy to LRTAP.  The study used empirical-normative research method sourcing from literatures and journals.  The study shows that ASEAN formed the Agreement on Transboundary Haze Pollution (ATHP) which has the aim of being a body that works to reduce and suppress air pollution in the ASEAN region, framed within the 1979 Convention on Long-Range Transboundary Air Pollution (LRTAP). In comparison to LRTAP, the aforementioned can be offered as a means of recommendation for the success of the AATHP. It is measurable that the importance placed on contribution, cooperation, scrutiny, democracy, and transparency in the agreement was a contributing factor in LRTAP's success.